2021
DOI: 10.3390/w13020170
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Electrical Sounding (VES) for Estimation of Hydraulic Parameters in the Porous Aquifer

Abstract: Similarities in both water and electric current flows allow the relation of hydraulic and geoelectric parameters of porous aquifers. Based on this assumption and the importance of the hydraulic parameters for groundwater analyses, this study aimed to estimate hydraulic conductivity (K) and transmissivity (T) with vertical electrical sounding (VES) in the porous aquifer at the experimental farm of the University of Brasilia, Brazil. VES is a geophysical technique that provides electrical resistivity (ρ, Ω m) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The aquifer hydraulic conductivity (K) describes the ease with which water can move through aquifer units. Hydraulic conductivity of a soil or rock or geological formation depends on various physical and geological variables including porosity, the structure of the soil matrix, grain size distribution, type of soil fluid, particle arrangement, water contents, void ratio, and other factors (Obiora et al, 2016;Almeida et al, 2021;Ibuot et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aquifer hydraulic conductivity (K) describes the ease with which water can move through aquifer units. Hydraulic conductivity of a soil or rock or geological formation depends on various physical and geological variables including porosity, the structure of the soil matrix, grain size distribution, type of soil fluid, particle arrangement, water contents, void ratio, and other factors (Obiora et al, 2016;Almeida et al, 2021;Ibuot et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The grain sizes range from coarse to fine in texture and are poorly sorted. The Benin Formation which occurs at shallower horizons comprises continental deposits of sand and gravel and is important in groundwater exploration (Almeida et al, 2021).…”
Section: Location and Geology Of The Study Areamentioning
confidence: 99%
“…The Dar Zarrouk parameters of the study area are observed by taking account of acquired resistivity and its corresponding thickness. By analyzing these Dar Zarrouk parameters, researchers can gain insights into the subsurface's ability to transmit fluids and obtain a better understanding of groundwater flow characteristics in the study area [31,74].…”
Section: Methodsmentioning
confidence: 99%
“…The measured resistivity not only gives the presence of an aquifer but also gives information about groundwater quality [24][25][26]. Vertical electrical sounding (VES) using the principle of resistivity gives reliable results about the groundwater, contamination, and lithological conditions based on resistivity contrast [27][28][29][30][31][32][33]. The progression of technology has led to the extensive acknowledgment of geoelectrical methods for groundwater detection, offering time, cost, and labor savings, along with improved drilling precision [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical electrical sounding (VES) is the most frequently used method in groundwater investigation to delineate potential groundwater zones and determine aquifer characteristics (Genedi and Youssef 2023;Mohammed et al 2023b). The VES approach was chosen for this study because it uses basic equipment, has simpler field logistics, and requires less time and resources to analyze data (Asfahani and Al-Fares 2021;de Almeida et al 2021). Several works have been documented in the literature on the effective use of the VES technique to delineate potential groundwater zones and model groundwater aquifer characteristics (Soomro et al 2019;Arunbose et al 2021;Omeje et al 2021;Oudeika et al 2021;Alarifi et al 2022;El Makrini et al 2022;George et al 2022;Gyeltshen et al 2022).…”
Section: Introductionmentioning
confidence: 99%